Ecological Education As The Most Important Problem Of Modern Education - S.U. Kistaubayev (Zien Journals, 2024)
In this article, the impact of environmental education - natural processes on the mind and worldview of young people was analyzed directly from the author's point of view. Environmental education is a form and part of education, the main goal of which is to observe the environment in the young generation, which is described in the article
Keywords: Ecological culture; feeding; ecological consciousness